Meta Analisis Efektivitas Pendekatan Problem Based Learning terhadap Kemampuan Berpikir Kritis Siswa Kelas V Sekolah Dasar - Riva Oktaviani; Naniek Sulistya Wardani (Jurnal Sekolah Dasar, 2023)
This study aims to re-analyze whether there is an effectiveness of the Problem Based Learning approach on the critical thinking skills of fifth grade elementary school students. This type of research is meta-analysis. Data obtained from previous research, summarized, reviewed, and then analyzed the research data, and by analyzing from several relevant sources that have been published thoroughly, which relates to using the Problem Based Learning (PBL) learning model on the critical thinking skills of fifth grade students. Elementary schools then obtain valid data. The research subjects were students of class V Elementary School. The data collection technique was by browsing e-journal articles through Google Scholar as many as 20 articles in the last 10 years (2012-2022). The research instrument was carried out using an observation sheet. The data analysis technique uses effect size and with the help of SPSS 26. From the overall effect size calculation, the average score obtained is 0.985455155 in the high category. So it can be concluded that there is an effectiveness of the Problem Based Learning approach on the critical thinking skills of fifth grade elementary school students.